Relationships between internet addiction, quality of life and sleep problems: a structural equation modeling analysis - Ferrari Junior G.J.* (2024)
© 2023 Sociedade Brasileira de PediatriaObjective: To assess the relationship between internet addiction, quality of life, and sleep problems among adolescents. Method: This research was conducted with a representative sample of 875 adolescents. This cross-sectional study used the Internet Addiction Test, Pediatric Quality of Life Inventory™ version 4.0, Pediatric Daytime Sleepiness Scale, and sleep duration. Sociodemographic factors were also analyzed. Structural equation modeling was used to investigate relationships between variables. Results: After adjusting the model for covariances between the latent variables of daytime sleepiness and correlations between the physical and emotional domains of quality of life, the authors obtained satisfactory fit indices (RMSEA = 0.031, CFI = 0.926, TLI = 0.909, SRMR = 0.058). Internet addiction was positively associated with daytime sleepiness (rho = 0.549, p < 0.001) and negatively associated with quality of life (rho = −0.173, p < 0.001). By contrast, sleep duration was negatively associated with daytime sleepiness (rho = −0.089, p = 0.007), positively associated with quality of life (rho = 0.105, p = 0.014), and dependent on school shift (rho = 0.453, p < 0.001). Conclusions: Adolescents with higher levels of internet addiction had lower perceptions of quality of life and higher daytime sleepiness. Moreover, sleep duration had a positive correlation with quality of life. Given its detrimental effects on quality of life and daytime sleepiness, parents should better supervise internet use in adolescents.